2015
DOI: 10.1007/s40265-015-0419-5
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine: A Review of Its Use for Sedation in the Intensive Care Setting

Abstract: Dexmedetomidine (Dexdor(®)) is a highly selective α2-adrenoceptor agonist. It has sedative, analgesic and opioid-sparing effects and is suitable for short- and longer-term sedation in an intensive care setting. In the randomized, double-blind, multicentre MIDEX and PRODEX trials, longer-term sedation with dexmedetomidine was noninferior to midazolam and propofol in terms of time spent at the target sedation range, as well as being associated with a shorter time to extubation than midazolam or propofol, and a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
228
1
17

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 290 publications
(248 citation statements)
references
References 61 publications
2
228
1
17
Order By: Relevance
“…[91][92][93] Dexmedetomidine Dexmedetomidine is a selective α 2 -agonist primarily used for sedation. 94,95 Despite its ability to decrease acute postoperative pain and improve long-term outcomes including a decreased incidence of postoperative complications including major adverse cardiac events, delirium, and overall mortality up to 1 year postoperatively, no evidence exists to support a decrease in chronic pain. 96,97 Glucocorticoids Glucocorticoids have an extensive history of use in cardiac surgery but the Steroids In Cardiac Surgery trial showed no difference in pain at 30 days or in chronic incisional pain at 6 months.…”
Section: Remifentanilmentioning
confidence: 99%
“…[91][92][93] Dexmedetomidine Dexmedetomidine is a selective α 2 -agonist primarily used for sedation. 94,95 Despite its ability to decrease acute postoperative pain and improve long-term outcomes including a decreased incidence of postoperative complications including major adverse cardiac events, delirium, and overall mortality up to 1 year postoperatively, no evidence exists to support a decrease in chronic pain. 96,97 Glucocorticoids Glucocorticoids have an extensive history of use in cardiac surgery but the Steroids In Cardiac Surgery trial showed no difference in pain at 30 days or in chronic incisional pain at 6 months.…”
Section: Remifentanilmentioning
confidence: 99%
“…It is necessary to mention that the use of DEX beyond 24 hours may be associated with a dose-related increase in adverse events and for this reason, the Food and Drug Administration (FDA) has not recommended the use of DEX for more than 24 hours [27,28] . However, the safe use of this drug has been reported from 24 hours to more than a week [28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these side effects occur at infusion of 0.2-0.7 mcg/kg/h without a bolus dose [28,31] . In our review, the occurrence of respiratory depression was low and reported only in one trials [14] , which is consistent with previous studies [11,28,31] . Previous study showed that respiratory suppression does not even occur at DEX plasma levels up to 8.0 ng/mL and only there is a risk of over-sedation [32] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations